Caracterização físico-química e extração dos pigmentos presentes em cascas de pitaia - Nakayama, Sumaya Hellú El Kadri (2020)
The dragon fruit is belonging to the Cactaceae family and known in the worldwide like an extremely attractive exotic fruit due to its sensory characteristics, color, and appearance. The interest in extracting the natural dyes present in pulp and peel of the dragon fruit has led to several studies regarding its extraction, characterization, and determination of the antioxidant activity of this fruit. The dragon fruit peel is considered a residue of food industry and it has a high amount of betalains in its composition, making it a promising source of these compounds for use as natural dyes in several segments. In this context, the aim of this work was to evaluate the physicochemical and spectroscopic characteristics of peels of white and red pulp dragon fruit. The proximate composition of the peels was determined according to the Analytical Norms of ITAL, and the carbohydrates content was calculated by difference. Simplex Centroid design for three components was used: aqueous solution of citric acid 2 %, ethanol and acetone and then, the extracts was lyophilized. Spectroscopic analysis in the UV-Vis and Infrared regions was performed with each extract and the spectral data were submitted to Principal Components Analysis (PCA). The parameters of the proximate composition showed a significant difference (p<0.05) between the peel parameters of the analyzed dragon fruits. The PCA of the spectral data in UV-Vis and FTIR showed that the peel of red pulp dragon fruit has a slightly higher content of pigments, acid compounds, polyphenolic and sugars than the peel of white pulp dragon fruit. The low protein content was confirmed by the FTIR. The use of dragon fruit peel is an option for the use of this residue, as a source of natural dyes and antioxidants.